A pressure-temperature phase diagram for zircon at extreme conditions - Timms, Nicholas; Erickson, Timmons; Pearce, M.; Cavosie, Aaron; Schmieder, M.; Tohver, E.; Reddy, Steven; Zanetti, M.; Nemchin, A.; Wittmann, A. (Elsevier BV, 2017)
Hypervelocity impact processes are uniquely capable of generating shock metamorphism, which causes mineralogical transformations and deformation that register pressure (P) and temperature (T) conditions far beyond even the most extreme conditions created by terrestrial tectonics. The mineral zircon (ZrSiO4) responds to shock deformation in various ways, including crystal-plasticity, twinning, polymorphism (e.g., transformation to the isochemical mineral reidite), formation of granular texture, and dissociation to ZrO2 + SiO2, which provide robust thermobarometers that record different extreme conditions. The importance of understanding these material processes is two-fold. First, these processes can mobilize and redistribute trace elements, and thus be accompanied by variable degrees of resetting of the U-Pb system, which is significant for the use of zircon as a geochronometer. Second, some features described herein form exclusively during shock events and are diagnostic criteria that can be used to confirm the hypervelocity origin of suspected impact structures. We present new P-T diagrams showing the phase relations of ZrSiO4 polymorphs and associated dissociation products under extreme conditions using available empirical and theoretical constraints. We present case studies to illustrate zircon microstructures formed in extreme environments, and present electron backscatter diffraction data for grains from three impact structures (Mistastin Lake of Canada, Ries of Germany, and Acraman of Australia) that preserve different minerals and microstructures associated with different shock conditions. For each locality, we demonstrate how systematic crystallographic orientation relationships within and between minerals can be used in conjunction with the new phase diagrams to constrain the P-T history. We outline a conceptual framework for a zircon-based approach to ‘extreme thermobarometry’ that incorporates both direct observation of high-P and high-T phases, as well as inferences for the former existence of phases from orientation relationships in recrystallised products, a concept we refer to here as ‘phase heritage’. This new approach can be used to unravel the pressure-temperature history of zircon-bearing samples that have experienced extreme conditions, such as rocks that originated in the Earth's mantle, and those shocked during impact events on Earth and other planetary bodies.